Latent fingermark detection using functionalised silicon oxide nanoparticles: Method optimisation and evaluation. (May 2019) - Lee, Po Lun Timothy; Kanodarwala, Fehmida K.; Lennard, Chris; Spindler, Xanthe; Spikmans, Val; Roux, Claude; Moret, Sébastien
Highlights: A luminescent carboxyl-functionalised SiO2 NPs method was modified, optimised and evaluated for fingermark detection. Lower NP concentration, increased bath temperature and reduced immersion time were found to produce good overall results. Performance of the modified and previously published detection parameters were compared. The overall performance of the modified method was deemed to be superior. Abstract: The application of nanoparticles for latent fingermark detection has been reported in the literature over the past two decades. One of the nanoparticles that shows promise to become a routine technique is functionalised silicon oxide nanoparticles (SiO2 NPs). In a recent optimisation of the technique, the use of carboxyl-functionalised SiO2 NPs doped with luminescent ruthenium complex was proposed as a breakthrough for latent fingermark detection. In this study, the aforementioned functionalised SiO2 NPs were extensively evaluated. Modification and optimisation of the original detection parameters were performed to enhance detection quality and improve applicability. Various detection parameters were evaluated and assessed. A lower concentration of the functionalised nanoparticles used in the colloidal dispersion was determined to offer improved detection effectiveness. A combination of increased bath temperature and reduced immersion time was found to produce good overall results. A set of modified detection parameters was suggested for the use of the functionalised SiO2 NPs to detect latent fingermarks. Performance of the modified detection parameters was compared against that of the published detection method. Comparison experiments were carried out on fingermark specimens deposited on aluminium foil, transparent polypropylene plastic and green polyethylene plastic. Three donors (weak, average and strong) and two age intervals (ten days and three months) were considered in the comparison study. Evaluation of the results suggested that the overall performance of the modified method for latent fingermark detection was superior to that obtained using the previously published detection parameters.